A Sol-Gel Approach for the Fabrication of Zinc Oxide Nanoparticles and Their Nanocomposite with Urea Formaldehyde (UF) - Hemantkumar N. Kohale; Sudhanshu Kharkate; Rakesh Naktode; Mangesh Thakare (International Journal of Crystalline Materials, 2025)
In the performed work, zinc oxide nanoparticles were synthesized via the sol-gel method using zinc sulphate as the precursor material. Urea-formaldehyde (UF) resin was employed as a polymer matrix to encapsulate the produced ZnO through an acid-catalyzed polymerization process. This encapsulation aimed to improve the dispersion stability and surface reactivity of ZnO within the polymeric medium. The synthesized materials were subjected to comprehensive characterization using Fourier Transform Infrared Spectroscopy (FT-IR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray Analysis (EDX). FT-IR spectra exhibited characteristic metal-oxygen stretching vibrations confirming the formation of ZnO bonds, while additional bands corresponding to functional groups in the UF resin indicated successful encapsulation. The XRD pattern showed sharp and well-defined peaks, signifying the highly crystalline nature of ZnO nanoparticles. SEM micrographs revealed that the particles possessed predominantly spherical morphology with uniform size distribution, suggesting controlled nucleation during synthesis. EDX analysis provided the elemental composition and verified the presence of zinc and oxygen as major constituents. Furthermore, the ZnO-UF nanocomposite demonstrated enhanced structural integrity, which could contribute to improved mechanical strength, thermal stability, and potential antimicrobial properties. Overall, the combined spectroscopic and microscopic analyses validated the successful synthesis and encapsulation of ZnO nanoparticles within the UF matrix. Additionally, the incorporation of ZnO nanoparticles into the UF resin matrix offers significant potential for diverse industrial and environmental applications. The encapsulation process not only prevents agglomeration but also enhances the durability and surface activity of the nanoparticles.
Keywords: Metal oxides; Nanoparticle; Sol-gel; resin; urea-formaldehyde